Diaconia e missão em contexto de periferia: o desafio da cidadania na comunidade de Bico do Urubu - Astore, Danuzio (2010)
This paper wants to contribute in the analysis of the specific reality of a community located in a peripheral region of Guarapari in Espírito Santo State. The work is guided in the assessment and consequent importance of volunteer work in churches and also in discovering the true meaning of the Mission and diakonia. This is to evaluate the second moment of theology, that is a reflection to get a first act that was the elaboration of a project to mitigate the social hardships of families living in the neighborhood Lameirão, in Guarapari. This first response is motivated by faith. In the Brazilian context, it is worth noting that evangelical churches today do not have to pay due attention to the Mission and Diakonia. Certainly, this work is a way to be rediscovering the importance of the contribution of Mission and Diakonia, not only the Church but to society.